2019
DOI: 10.1108/mrr-12-2018-0494
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fair supervision on employees’ emotional exhaustion and turnover intentions

Abstract: PurposeDespite the importance of interactional fairness, it has been assessed less frequently in literature than has procedural and distributive justice. The effects of interactional fairness are at times stronger than the effects for procedural and distributive fairness, given that supervisors are prominent in any workplace environment and the chief source for interpreting information related to matters such as suitable business practices and goals needed by organizations. This study aims to examine the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
(74 reference statements)
1
10
1
7
Order By: Relevance
“…The results of the structural model of the influence of burnout on turnover intention are positive (β = 0.359), so it can be stated that the second hypothesis model (H2) that was built is acceptable. The findings of this model are supported by (Avanzi et al, 2014;Campbell et al, 2013;Choi et al, 2012;Elçi et al, 2018;Kyei-Poku, 2019;Mosadeghrad, 2013;Santhanam & Srinivas, 2019;Srivastava & Agrawal, 2020;Willard-Grace et al, 2019) found that there is a positive influence between burnout on turnover intention. These results provide an understanding that when employees feel work stress that is not excessive or emotional fatigue will make employees feel calm and understand the environmental conditions of the organization, both physical and non-physical so that they do not intend to leave the organization or company.…”
Section: B Burnout Has a Positive Effect On Turnover Intentionsupporting
confidence: 57%
See 2 more Smart Citations
“…The results of the structural model of the influence of burnout on turnover intention are positive (β = 0.359), so it can be stated that the second hypothesis model (H2) that was built is acceptable. The findings of this model are supported by (Avanzi et al, 2014;Campbell et al, 2013;Choi et al, 2012;Elçi et al, 2018;Kyei-Poku, 2019;Mosadeghrad, 2013;Santhanam & Srinivas, 2019;Srivastava & Agrawal, 2020;Willard-Grace et al, 2019) found that there is a positive influence between burnout on turnover intention. These results provide an understanding that when employees feel work stress that is not excessive or emotional fatigue will make employees feel calm and understand the environmental conditions of the organization, both physical and non-physical so that they do not intend to leave the organization or company.…”
Section: B Burnout Has a Positive Effect On Turnover Intentionsupporting
confidence: 57%
“…Choi et al, (2012) also used these 3 dimensions in their study (emotional fatigue, depersonalization, and reduced personal achievement). Several studies have found that there is a positive influence between burnout on turnover intention (Avanzi et al, 2014;Campbell et al, 2013;Choi et al, 2012;Elçi et al, 2018;Kyei-Poku, 2019;Mosadeghrad, 2013;Santhanam & Srinivas, 2019;Srivastava & Agrawal, 2020;Willard-Grace et al, 2019). On this basis as a reference in building a research model, it can be indicated that:…”
Section: Burnout and Turnover Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional exhaustion is an effect on different factors like sexualization of the work environment (Bui, Pinto, & Srivastava, 2019), long term customer relationships development (Lee & Huang, 2020), Machiavellian leadership (Stradovnik & Stare, 2018), emotion regulation (reappraisal & suppression) (Lee & Jang, 2019), task-level job demand (Laila & Hanif, 2017), turnover intention (Kyei-Poku, 2019;Park, 2019), work intensity and life satisfaction (Boekhorst, Singh, & Burke 2017), workplace incivility (Alola, Avci, & Ozturen, 2020;Karatepe, Kim, & Lee, 2019;Tong, Chong, & Johnson, 2019), and perceived organizational politics (Makhdoom, Mehmood, & Atta, 2017;Naseer, Raja, & Donia, 2016). Extant literature revealed that the effect of perceived organizational politics and workplace incivility is significant on exhaustion comparative to other predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Ini adalah disebabkan faktor yang penting bagi membangunkan sokongan organisasi adalah dengan meningkatkan keadilan (Eisenberger & Stinglhamber 2011). Beberapa kajian -kajian lepas mendapati keadilan prosedur mempunyai hubungan yang positif terhadap sokongan organisasi (Arnéguy et al 2022;Kyei-Poku 2019;Nazir et al 2019;Rubel et al 2020). Oleh itu, hipotesis yang dibina berdasarkan kajian lepas adalah seperti berikut:…”
Section: Keadilan Prosedur (Formal) Dan Sokongan Organisasiunclassified